BOOK REVIEW: SPORT, LEISURE AND SOCIAL JUSTICE - Kacper Madej (Society Register)
Sport leisure and social justice is an important and essential book central to its theme. Editors present a collection of research analysis presented on a variety of different cases. Readers are introduced to a diversity of experiences of marginalized categories of people, theoretical approaches and contexts (e.g. physical education, musical events) that can be used in regards to inequality in this field.